Bone geometry, strength, and muscle size in runners with a history of stress fracture - Popp, K. L.; Hughes, J. M.; Smock, A. J.; Novotny, S. A.; Stovitz, S. D.; Koehler, S. M.; Petit, M. A. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Our primary aim was to explore differences in estimates of tibial bone strength, in female runners with and without a history of stress fractures. Our secondary aim was to explore differences in bone geometry, volumetric density, and muscle size that may explain bone strength outcomes.